Patients Of Eat Intake In Children Who Have Obesity And Overweight In The Mountains And Coastal Areas - Asnidar; Irfanita Nurhidayah; Risnawati (Jurnal Life Birth, 2018)
According to the World Health Organization (WHO), The prevalence of overweight and obesity in children in the world increased by 6.7% in 2010 and is expected to reach 9.1% in 2020. From the results of preliminary data collection in several schools including in the mountainous region namely SMPN 14 Tanete with 180 VII grade VII students and 18 Bulukumba SMP with 51 VII Grade VII students, while in the coastal area that is 32 Bulukumba SMPN with 210 VII Grade VII students. Total of the total population of the four schools in the mountainous and coastal areas as many as 441 students. The purpose of this study is to analyze the differences in food intake patterns in children who are obese and overweight in mountainous and coastal areas. This research method uses descriptive research with a comparative study approach. The total population of this study was 441. With samples in the mountainous region, 35 respondents and 33 respondents were sampled a total of 68 respondents with consecutive sampling techniques. So it can be concluded that the distribution of eating patterns is less prevalent in overweight children and the distribution of eating patterns is more prevalent in obese children. Researchers suggest that the results of this study can provide information on the dietary intake of children who are obese and overweight in mountainous and coastal areas in Bulukumba Regency 2018. For parents of students, there is an awareness to behave in a healthy life by paying attention to food and limiting instant foods as well as oily foods such as fried foods.